Case report: An interesting case of large colloid goiter with dyspnea - Mayya, Jaya Prakasha; Gautam, Nabin; Pokharel, Apar; Pandey, Bikash (Journal of College of Medical Sciences-Nepal, 2017)
Benign nodular goitre is one of the most common endocrine disorder, especially in countries like Nepal where iodine deficiency is endemic. Case History: A 59 years old female presented with large thyroid swelling. Investigations showed it to be colloid goiter compressing the airway. Left hemithyroidectomy was done. Post operative period was uneventful. Discussion: Management of thyroid nodules depends upon assessment of thyroid function, fine needle aspiration cytology and imaging. Surgery is the common method of treatment.